Empire burlesque the fate of critical culture in global America - O'Hara, Daniel T. 1948- (Duke University Press, 2003)
Edward W. Said and the fate of critical culture -- Why Foucault no longer matters -- Lentricchia's frankness and the place of literature -- Redesigning the lessons of literature -- The return to ethics and the specter of reading -- Class in a global light : the two professions -- Transference and abjection : an analytic parable -- Ghostwork : an uncanny prospect for new Americanists -- Specter of theory : the bad conscience of American criticism -- Empire baroque : becoming other in Henry James -- Planet buyer and the catmaster : a critical future for transference
Includes bibliographical references (p. [357]-364) and index
Keywords: Criticism / History / 20th century / United States; American literature / History and criticism / Theory, etc; Literature / History and criticism / Theory, etc; Mass media and culture / United States; Journalism / United States